George Lucas : a life - Jones, Brian Jay (Little, Brown and Company, 2016)
"The best-selling author of Jim Henson: The Biography traces the story of the man behind such blockbuster franchises as Star Wars and Indiana Jones, offering insight into the challenges he overcame and his influential legacy,"--NoveList.